Linked lives : improving health and well-being in a complex world : Family and Community Health (FCH) highlights 2001-2002 (WHO GenevaCH, 2003)
Describes the structure and principle areas of activity of the WHO Family and Community Health (FCH) cluster during the period 2001-2002.
Keywords: FAMILY HEALTH